(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Antioxidants are the chemical substances which prevent the free radicals damage in the body. Numerous researches are going globally focussed on investigating natural antioxidants of plants origins. The aims of the present study were to evaluate preliminary phytochemical investigation and in vitro antioxidant activities of Ethiopian indigenous medicinal plants, Ocimum lamiifolium Hochst. ex Benth and Ocimum basilicum L. Aqueous, benzene and hexane crude leaves extracts of O. lamiifolium and O. basilicum were subjected to qualitative phytochemical screening using standard procedures. In addition, we investigated the antioxidant potential of crude aqueous leaves extract of O. lamiifolium and O. basilicum using tests involving inhibition of superoxide anions, DPPH, H2O2, NO and ABTS. Preliminary phytochemical investigation for benzene, hexane and aqueous extracts found alkaloids, sterols, carbohydrate and glycosides, tannins and flavonoids. The fraction inhibition of lipid peroxide at the first stage of oxidation illustrated antioxidant activity of O. lamiifolium and O. basilicum as 90% and 88% compared to those of gallic acid (97%) and BHT (84%) respectively. Also, the aqueous leaves extract of O. lamiifolium and O. basilicum exhibited significant DPPH free radical scavenging activity, nitric acid free radical scavenging activity assay, superoxide anion scavenging activity, ABTS scavenging activity and hydrogen peroxide free radical scavenging assay. Our findings provide confirmation that the aqueous leaves extract of O. lamiifolium and O. basilicum are potential source of natural antioxidants, and this warranted its uses in traditional medicine systems.